2018
DOI: 10.1111/cdev.13203
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Sequence and Relations Between Gesture and Spoken Language in Toddlers With Autism Spectrum Disorder

Abstract: In typical development, gestures precede and predict language development. This study examines the developmental sequence of expressive communication and relations between specific gestural and language milestones in toddlers with autism spectrum disorder (ASD), who demonstrate marked difficulty with gesture production and language. Communication skills across five stages (gestures, word approximations, first words, gesture-word combinations, and two-word combinations) were assessed monthly by blind raters for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 51 publications
2
12
1
Order By: Relevance
“…The finding that the onset of referential expressive language preceded the onset of declarative point for 89% of the toddlers with WS in the present sample replicates Mervis and Bertrand’s (1997) finding that 90% of an independent and considerably smaller sample of children with WS began to produce referential language prior to comprehending or producing declarative pointing gestures. This pattern contrasts strongly with that both for TD infants and for toddlers with a variety of other DDs (see review in Mervis and Bertrand, 1997) but fits with Talbott et al’s (in press) finding that in a sample of children with ASD, only 38% produced distal pointing gestures prior to the onset of expressive language. As discussed in the next section, this delay in the onset of referential gestures likely is an important contributor to the language delay associated with WS.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The finding that the onset of referential expressive language preceded the onset of declarative point for 89% of the toddlers with WS in the present sample replicates Mervis and Bertrand’s (1997) finding that 90% of an independent and considerably smaller sample of children with WS began to produce referential language prior to comprehending or producing declarative pointing gestures. This pattern contrasts strongly with that both for TD infants and for toddlers with a variety of other DDs (see review in Mervis and Bertrand, 1997) but fits with Talbott et al’s (in press) finding that in a sample of children with ASD, only 38% produced distal pointing gestures prior to the onset of expressive language. As discussed in the next section, this delay in the onset of referential gestures likely is an important contributor to the language delay associated with WS.…”
Section: Discussionsupporting
confidence: 78%
“…More recently, this relation has been addressed for toddlers with ASD. In a longitudinal study with monthly data collection, Talbott et al (in press) found a different pattern than had been reported for TD infants or children with other DDs. In particular, of the 32 participants, only 12 showed the typical pattern of acquisition of distal pointing gestures prior to the onset of expressive language.…”
Section: Introductioncontrasting
confidence: 55%
“…Özçalışkan et al (2016) found that the deictic gestures of 30month-old children with ASD could predict the vocabulary 1 year later. Besides, the emergence of distal pointing was closely linked with the emergence of first words, and the onset of gesture + word combinations predates and predicts the onset of two-word combinations (Talbott et al, 2018). In adolescence, gesture use was positively associated with vocabulary for youths with ASD (Medeiros and Winsler, 2014).…”
Section: Gestures In Children With Autism Spectrum Disordermentioning
confidence: 91%
“…Thus, improvements in AP may reflect an increase in the frequency with which children used these skills, rather Learning a new behaviour may also take more time than increasing the consistency with which an already acquired behaviour is used. This is likely to be especially true for learning new complex behaviours such as language where development tends to occur in stages over time (Rogers & Dawson, 2010;Talbott et al, 2018). It may therefore be difficult to show progress in these types of behaviours in studies conducted over a relatively short time period, such as Studies 1 and 2.…”
Section: Child Outcomesmentioning
confidence: 99%
“…Finally, it is worth noting that an estimated 25 -30% of individuals with ASD may never develop productive speech (Talbott et al, 2018). It is therefore possible that for this subset of the ASD population, intervention may not lead to improvements on verbal outcomes.…”
Section: Vocal/verbal Outcomesmentioning
confidence: 99%